Intensity and correlates of gender prejudices in the residents of Vojvodina - Mihić, Vladimir (Primenjena psihologija, 2010)
The research presented in this paper dealt with the correlates of the sexism, namely, prejudices toward women, but also prejudice toward men. The sample consisted of 604 subjects from Vojvodina, age 17 to 51, gender-balanced. We also took into account subjects' education, place of birth, employment and socio-economic status. Instruments used were: Rosenberg self-esteem scale, social dominance orientation scale, AutoritarNoSt, ambivalent sexism inventory – ASI and ambivalence toward men inventory - AMI. Results show that important correlates were gender, education, socio-economic status and the place of birth of the respondents, but also authoritarianism, social dominance orientation, self-esteem and the strength of the social identity.